Effects of red dragon fruit (hylocereus polyrhizus) skin extract on lead acetate toxicity in the morphology of balb/c mice (mus musculus) spermatozoa - Raharjo, Rahmawati; Sudjarwo, Sri Agus; I'tishom, Reny (Folia Medica Indonesiana, 2017)
Red dragon fruit skin extract is used as an antioxidant to lead acetate toxicity. This study aimed to prove the difference in morphology of mice testicular spermatozoa exposed to lead acetate. Twenty-five mice were divided into 5 groups (5 mice per group). K- group was the control group without lead acetate and dragon fruit skin extract administration, K + group was treated with 8 mg/KgBW lead acetate administration for 14 days, P1 group was treated with the administration of 8 mg/KgBW lead acetate for 14 days + 250 mg/kgBW red dragon fruit skin extract for 21 days, P2 group was treated with the administration of 8 mg/KgBW lead acetate for 14 days + 500 mg/kgBW red dragon fruit skin extract for 21 days, and group P3 was a treatment group with the administration of 8 mg/KgBW lead acetate for 14 days + 1000 mg/kgBW red dragon fruit extract for 21 days. The results showed that there was significant difference (P<0.05) in normal sperm morphology among K-, K +, P1, P2, and P3. In conclusion, the administration of red dragon skin extract at a dose of 500 mg/kgBW (P2) is the optimal one which can be used as therapy to increase motility, morphology, and concentration of mice spermatozoa exposed to lead acetate.